Effects of Sport-Specific Training during the Early Stages of Long-Term Athlete Development on Physical Fitness, Body Composition, Cognitive, and Academic Performances - Granacher, Urs; Borde, Ron (Frontiers in Physiology, 2017)
Introduction: Several sports demand an early start into long-term athlete development (LTAD) because peak performances are achieved at a relatively young age (e.g., gymnastics). However, the challenging combination of high training volumes and academic demands may impede youth athletes’ cognitive and academic performances. Thus, the aims of this study were to examine the effects of a one-year sport-specific training and/or physical education on physical fitness, body composition, cognitive and academic performances in youth athletes and their non-athletic peers. Methods: Overall, 45 prepubertal fourth graders from a German elite sport school were enrolled in this study. Participating children were either youth athletes from an elite sports class (n=20, age 9.5±0.5 years) or age-matched peers from a regular class (n=25, age 9.6±0.6 years). Over the one-year intervention period, the elite sports class conducted physical education and sport-specific training (i.e., gymnastics, swimming, soccer, bicycle motocross [BMX]) during school time while the regular class attended physical education only. Of note, BMX is a specialized form of cycling that is performed on motocross tracks and affords high technical skills. Before and after intervention, tests were performed for the assessment of physical fitness (speed [20-m sprint], agility [star agility run], muscle power [standing long jump], flexibility [stand-and-reach], endurance [6-min-run], balance [single-leg stance]), body composition (e.g., muscle mass), cognitive (d2-test) and academic performance (reading [ELFE 1-6], writing [HSP 4-5], calculating [DEMAT 4]). In addition, grades in German, English, Mathematics, and physical education were documented. Results: At baseline, youth athletes showed better physical fitness performances (p<0.05; d=0.70–2.16), less relative body fat mass, more relative skeletal muscle mass (p<0.01; d=1.62–1.84), and similar cognitive and academic achievements compared to their non-athletic peers. Athletes’ training volume amounted to 620 min/week over the one-year period while their peers performed 155 min/week. After the intervention, significant differences were found in 6 out of 7 physical fitness tests (p<0.05; d=0.75–1.40) and in the physical education grades (p<0.01; d=2.36) in favor of the elite sports class. No significant between-group differences were found after the intervention in measures of body composition (p>0.05; d=0.66–0.67), cognition and academics (p>0.05; d=0.40–0.64). Our findings revealed no significant between-group differences in